2018
DOI: 10.1177/0886260518755486
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Cultural Factors on Dating Aggression and Delinquency Among Latino Youth

Abstract: There is limited research comparatively evaluating delinquency and dating aggression among Latino youth. This analysis examines the rates and cultural correlates associated with delinquency and dating aggression among Latino youth using data from the Dating Violence Among Latino Adolescents study. The study surveyed 1,525 Latino adolescents between the ages of 12 and 18 years about past-year dating aggression perpetration and delinquency. Dating aggression perpetration and delinquency rates and relative risk r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 75 publications
0
7
0
Order By: Relevance
“…Examining the influence of the segmented assimilation perspective on Latinos and offending behavior, Gibson and Miller (2010) found support for the cultural retention perspective in that cultural retention that occurred in immigrant neighborhoods served as a protective factor toward offending. In a study of Latino youth, Cuevas et al (2018) found an association between greater acculturation to American society and dating aggression, but did not establish this link in delinquent behavior more broadly. Other research found support for the link between acculturation to U.S. mainstream norms and gang membership among Latinos; however, this relationship is partially mediated by ethnic marginalization (Miller et al, 2011).…”
Section: Acculturation and Cultural Retentionmentioning
confidence: 88%
See 1 more Smart Citation
“…Examining the influence of the segmented assimilation perspective on Latinos and offending behavior, Gibson and Miller (2010) found support for the cultural retention perspective in that cultural retention that occurred in immigrant neighborhoods served as a protective factor toward offending. In a study of Latino youth, Cuevas et al (2018) found an association between greater acculturation to American society and dating aggression, but did not establish this link in delinquent behavior more broadly. Other research found support for the link between acculturation to U.S. mainstream norms and gang membership among Latinos; however, this relationship is partially mediated by ethnic marginalization (Miller et al, 2011).…”
Section: Acculturation and Cultural Retentionmentioning
confidence: 88%
“…In a study of Latino youth, Cuevas et al. () found an association between greater acculturation to American society and dating aggression, but did not establish this link in delinquent behavior more broadly. Other research found support for the link between acculturation to U.S. mainstream norms and gang membership among Latinos; however, this relationship is partially mediated by ethnic marginalization (Miller et al., ).…”
Section: Literature Reviewmentioning
confidence: 97%
“…Others have found that acculturation is not related to delinquency and is instead negatively associated with dating aggression (Cuevas et al, 2018). However, some have found that the theory still explains being victimized at school as well as receiving disciplinary sanctions at school (Peguero, 2008).…”
Section: Criminology and Segmented Assimilation Theorymentioning
confidence: 99%
“…Participants were allowed to answer 13 victimization questions with a yes or no response (0 ¼ no, 1 ¼ yes). Following previous studies that have used these data (Cudmore et al, 2017;Cuevas et al, 2018), poly-victimization was operationalized as the total number of victimizations that happened in the past year irrespective of the number of the actual incidents in any one category (a ¼ .68).…”
Section: Demographic and Control Variablesmentioning
confidence: 99%
“…Second, a growing body of literature has begun to uncover the correlates of dating violence among Latino youth. Studies have generally examined this issue in the context of cultural aspects such as acculturation, enculturation, gender stereotypes, machismo, and marianismo (Alvarez et al, 2018;Cuevas et al, 2018;Terrazas-Carrillo & Sabina, 2019;Ulloa et al, 2004). These cultural aspects are important because of their influence on the relationship dynamics within Latino dating culture (Lopez et al, 2012).…”
mentioning
confidence: 99%